“I Felt Pressured to Give 100% All the Time”: How Are Neurodivergent Professionals Being Included in Software Development Teams? - Menezes, Nicoly da Silva; Rocha, Thayssa Águila da; Camelo, Lucas Samuel Santiago; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: As the demand for digital solutions adapted to different user profiles increases, creating more inclusive and diverse software development teams becomes an important initiative to improve software product accessibility. Problem: However, neurodivergent professionals are underrepresented in this area, encountering obstacles from difficulties in communication and collaboration to inadequate software tools, which directly impact their productivity and well-being. Solution: This study seeks to understand the work experiences of neurodivergent professionals acting in different software development roles. A better understanding of their challenges and strategies to deal with them can collaborate to create more inclusive software development teams. IS Theory: We applied the Sociotechnical Theory (STS) to investigate how the social structures of organizations and their respective work technologies influence the inclusion of these professionals. Method: To address this study, we conducted semi-structured interviews with nine neurodivergent professionals in the Software Engineering field and analyzed the results by applying a continuous comparison coding strategy. Results: The results highlighted issues faced by interviewees, the main ones related to difficulties in communication, social interactions, and prejudice related to their diagnosis. Additionally, excessive in work tools became a significant challenge, leading to constant distractions and cognitive overload. This scenario negatively impacts their concentration and overall performance. Contributions and Impact in the IS area: As a contribution, this study presents empirically based recommendations to overcome sociotechnical challenges faced by neurodivergent individuals working in software development teams.